2009
DOI: 10.1111/j.1365-3083.2008.02217.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Circulating Levels of IFN‐γ, IL‐10, CXCL9 and CCL2 in Pulmonary and Extrapulmonary Tuberculosis is Dependent on Disease Severity

Abstract: Protection against Mycobacterium tuberculosis infection is dependent on T cell and macrophage activation regulated by cytokines. Cytokines and chemokines produced at disease sites may be released into circulation. Data available on circulating cytokines in tuberculosis (TB) is mostly on pulmonary TB (PTB) with limited information on extrapulmonary disease (EPul‐TB). We measured interferon‐gamma (IFN‐γ), interkeukin‐10 (IL‐10), CXCL9 and CCL2 in sera of patients (n = 80) including; PTB (n = 42), EPul‐TB (n = 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 35 publications
2
42
0
8
Order By: Relevance
“…Concordant with the raised levels of ESAT6 induced IFN-γ secretion observed [23], ESAT6-induced IFN-γ mRNA expression levels were increased in the EC ESAT6 IFN-γ (+),as compared with EC ESAT6 IFN-γ (-) cases (p = 0.019), Figure 2A. Also, ESAT6-induced IFN-γ expression levels were raised in PTB (p = 0.039) and ETB (p = 0.010) as compared with EC ESAT6-induced IFN-γ(-) cases .…”
Section: Differential Esat6-induced Socs1 Expression Between Healthy supporting
confidence: 50%
See 1 more Smart Citation
“…Concordant with the raised levels of ESAT6 induced IFN-γ secretion observed [23], ESAT6-induced IFN-γ mRNA expression levels were increased in the EC ESAT6 IFN-γ (+),as compared with EC ESAT6 IFN-γ (-) cases (p = 0.019), Figure 2A. Also, ESAT6-induced IFN-γ expression levels were raised in PTB (p = 0.039) and ETB (p = 0.010) as compared with EC ESAT6-induced IFN-γ(-) cases .…”
Section: Differential Esat6-induced Socs1 Expression Between Healthy supporting
confidence: 50%
“…Cells were lysed with Trizol reagent (Invitrogen, USA) and total RNA isolated as described previously [22,23]. RNA (1µg) was reverse transcribed using MulV reverse transcriptase (Invitrogen, Grand Island, New York USA) as described [24].…”
Section: Reverse Transcription-pcrmentioning
confidence: 99%
“…Some have found similar cytokine levels in sera from persons with various TB manifestations (40), while others such as Hasan et al found that circulating levels of cytokines such as IFN-␥ and CXCL9 differ based on the site of TB disease (19,40). Other groups have stimulated whole blood or PBMCs from persons with various forms of TB and measured cytokine levels and T lymphocyte proliferation (20,21,36,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that IFN-␥ plays a key role in exacerbating inflammation in the presence of IL-4 and IL-5. Indeed, IFN-␥ has also been associated with the development of mycobacterium-induced caseous necrosis, with excessive amounts of this cytokine contributing to the pathology observed in tuberculous patients (2,13,15,22,43).…”
Section: Discussionmentioning
confidence: 99%